Local community perceptions of disaster tourism: the case of L'Aquila, Italy. Issue 14 (22nd September 2018) - Wright, Daniel; Sharpley, Richard
Abstract : Despite increasing research in dark tourism, few attempts have been made to explore local community perceptions of becoming the object of the dark tourist gaze, an issue that is of particular relevance at disaster sites given the potential sensitivity of local people to the intrusion of tourists in the aftermath of a disaster. This paper addresses this significant gap in the literature. Based on research undertaken in L'Aquila, an Italian city that in April 2009 suffered a devastating earthquake, it explores the responses of members of the local community to their city becoming a dark (disaster) tourism destination. In so doing, it reveals an evolving response towards tourism that not only contradicts traditional understandings of resident perceptions of tourism, but also points towards how appropriate responses to disaster tourism might support the disaster recovery process.